The National Farmers Union: Working for Farm Families for 40 Years. - National Farmers Union (Canada) (National Farmers Union, 2009)
The NFU was formed in 1969 through a merger of the Saskatchewan Farmers Union, the Ontario Farmers Union, the Farmers Union of British Columbia, and the Farmers Union of Alberta. In addition to these provincial unions, farmers from the Maritime provinces—not organized into farmers’ unions at the time—also became part of the NFU structure. Prior to ’69, these provincial unions each had worked autonomously in its respective province, but increasingly they were finding themselves at a disadvantage in attempting to work with the federal government. In an effort to solve that problem, the unions created a coordinating body, the National Farmers Union Council, consisting of representatives of the executives of each provincial union and representatives from the Maritime provinces. Over time, the officials and members from the provincial unions and the Maritimes realized that the major policy decisions affecting farmers were being made at the federal level. At a joint meeting of the executives of the provincial unions and others in Winnipeg in March 1968, the executive members passed a motion to strike a committee to develop a constitution for a direct membership national farm organization. The founding convention of the National Farmers Union was held in Winnipeg in July 1969. In the following months the provincial unions were phased out and their assets and liabilities transferred to the national organization. –Publisher's description
OCLC: 816820748